1999
DOI: 10.2337/diabetes.48.12.2398
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of antioxidants in diabetes: possible protection of pancreatic beta-cells against glucose toxicity.

Abstract: Oxidative stress is produced under diabetic conditions and possibly causes various forms of tissue damage in patients with diabetes. The aim of this study was to examine the involvement of oxidative stress in the progression of pancreatic beta-cell dysfunction in type 2 diabetes and to evaluate the potential usefulness of antioxidants in the treatment of type 2 diabetes. We used diabetic C57BL/KsJ-db/db mice, in whom antioxidant treatment (N-acetyl-L-cysteine [NAC], vitamins C plus E, or both) was started at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
506
3
17

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 656 publications
(558 citation statements)
references
References 10 publications
32
506
3
17
Order By: Relevance
“…Because in previous research only post-transcriptional regulation of Pdx1 expression and function by ROS or antioxidant has been suggested [6,20,23,25], our finding on the hyperacetylation of H3 and H4 histone at the proximal promoter of Pdx1 in the OE mice reveals not only a novel, in vivo epigenetic, but also a potential transcriptional regulation for this key factor by antioxidant enzymes. Preceding transcriptional activation [43], hyperacetylation of H3 and H4 helps remodel the chromatin at Pdx1 promoter to form a more accessible structure for transcription [44].…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Because in previous research only post-transcriptional regulation of Pdx1 expression and function by ROS or antioxidant has been suggested [6,20,23,25], our finding on the hyperacetylation of H3 and H4 histone at the proximal promoter of Pdx1 in the OE mice reveals not only a novel, in vivo epigenetic, but also a potential transcriptional regulation for this key factor by antioxidant enzymes. Preceding transcriptional activation [43], hyperacetylation of H3 and H4 helps remodel the chromatin at Pdx1 promoter to form a more accessible structure for transcription [44].…”
Section: Discussionmentioning
confidence: 54%
“…Along with a modest decrease (24%) in pancreatic PDX1 phosphorylation (degradation) [25], the upregulation of Pdx1 gene expression enabled the OE mice to maintain a higher level of functional PDX1 protein than the WT mice to promote beta cell differentiation and insulin synthesis. While similar positive effects on PDX1 protein were produced by three dietary antioxidant supplements in C57BL/KsJ-db/db mice [23], overproduction of catalase in beta cells accelerated cytokine-induced PDX1 protein disappearance [9]. It is intriguing to see such different impacts on PDX1 protein by GPX1 and catalase, given the so similar catalytic functions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The fact that exendin-4 treatment was able to attenuate D-galactose-induced reduction of insulin secretion suggests that exendin-4 can alter oxidant signaling. The observations by Kaneto et al [25] showed that catalase and SOD can protect ß-cells against ROS-induced damage. Also, antioxidant treatment can suppress apoptosis of ß-cells and preserve ß-cell function in diabetic mice.…”
Section: Resultsmentioning
confidence: 99%